Second to Fourth Digit Ratio and Exercise Performance in Untrained Adult Males - A-K. Younes, Mohammed; M. Sulaiman, Shakir (Tikrit Journal of Pharmaceutical Sciences, 2023)
This study was based on a random sample from a Prospective Cohort study including one hundred healthy young untrained male volunteers, with mean age ± standard deviation (SD) of 22.820 ± 2.271 years. The aim of this study was to evaluate the role of the digit ratio as an indicator for the performance of untrained adult males in endurance sports. The parameters that have been measured were: Index and ring fingers length of both right and left hand, body weight, height, waist and hip circumferences, body composition (including: fat, muscle and water percents) and exercise performance (including: distance and time). The descriptive analyses of this study showed that normative values of male 2D:4D ratio vary between 0.912-1.036. and it also revealed that there is a strong inverse relation-ship between digit ratio of the subjects and exercise performance according to the distance and time; as the subject briskly walked on the treadmill at fasting state